(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Demographic changes are shaping new social, economic, and political trends globally. Key factors such as birth and mortality rates, population aging, urbanization, and migration significantly impact labor markets and workforce availability. While demographic shifts can create economic growth opportunities, they also pose challenges such as labor shortages, pension system pressures, and increased social security demands. The demographic transition model explains population growth patterns and their effects on economic development. Countries must implement strategic policies to address workforce imbalances, ensure sustainable economic growth, and adapt to changing demographic dynamics.